Review of the Cretaceous avian diversity of Antarctica: a changing scenario for the evolution of early Neornithine birds - Acosta Hospitaleche, Carolina Ileana Alicia (2024)
The worldwide record of Cretaceous Neornithes and Neornithine-like birds is both controversial and poorly understood. However, in recent years, the Antarctic continent has yielded a substantial number of Maastrichtian avian specimens, contributing significantly to our understanding of the early evolution of this group. Simultaneously, the keen interest and collaborative efforts of various paleornithologists have resulted in a wealth of knowledge, which we have thoroughly reviewed, updated, and discussed in the context of recent discoveries.